Global Occurrence of Clinically Relevant Hepatitis B Virus Variants as Found by Analysis of Publicly Available Sequencing Data - Velkov, Stoyan (Viruses, 2020)
Several viral factors impact the natural course of hepatitis B virus (HBV) infection, the sensitivity of diagnostic tests, or treatment response to interferon-α and nucleos(t)ide analogues. These factors include the viral genotype and serotype but also mutations affecting the HBV surface antigen, basal core promoter/pre-core region, or reverse transcriptase. However, a comprehensive overview of the distribution of HBV variants between HBV genotypes or different geographical locations is lacking. To address this, we performed an in silico analysis of publicly available HBV full-length genome sequences. We found that not only the serotype frequency but also the majority of clinically relevant mutations are primarily associated with specific genotypes. Distinct mutations enriched in certain world regions are not explained by the local genotype distribution. Two HBV variants previously identified to confer resistance to the nucleotide analogue tenofovir in vitro were not identified, questioning their translational relevance. In summary, our work elucidates the differences in the clinical manifestation of HBV infection observed between genotypes and geographical locations and furthermore helps identify suitable diagnostic tests and therapies.